2019
DOI: 10.1352/1944-7558-124.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of OSA Among an Adult Population With Down Syndrome Referred to a Medical Clinic

Abstract: Obstructive sleep apnea (OSA) is a common sleep disorder affecting approximately 16% of adults (24% of men and 9% of women), and, if untreated, it can cause significant complications (Young, 2009). This study evaluates 56 adult patients with Down syndrome and analyzed retrospective data to determine the: (1) prevalence of OSA, (2) severity of OSA, and (3) association between body mass index (BMI) and OSA. Of those participants that had polysomnography (PSG) testing available, 82.1% were diagnosed with OSA, div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…With 157 adult DS patients with proven OSA, ours is the largest study in adult DS population to date. Half of our patients had severe OSA, similar to the 69% reported by others (Cornacchia, Sethness, Alapat, Lin, & Peacock, 2019; Trois et al, 2009). Our study does not directly measure overall prevalence of OSA in DS adults, as sleep studies were not routinely performed in all DS patients, but only in those with a clinical suspicion and presumed CPAP feasibility (roughly 11% of the total cohort).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…With 157 adult DS patients with proven OSA, ours is the largest study in adult DS population to date. Half of our patients had severe OSA, similar to the 69% reported by others (Cornacchia, Sethness, Alapat, Lin, & Peacock, 2019; Trois et al, 2009). Our study does not directly measure overall prevalence of OSA in DS adults, as sleep studies were not routinely performed in all DS patients, but only in those with a clinical suspicion and presumed CPAP feasibility (roughly 11% of the total cohort).…”
Section: Discussionsupporting
confidence: 91%
“…With this limitation in mind, adults with DS may have a prevalence of OSA much higher than the general population, probably related to the morphology of the upper airway, a shorter and thicker neck, and associated overweight, as observed in our study and in others (Dudoignon et al, 2017; Gimenez et al, 2018; Young, 2009). Indeed, a recent study reported severe OSA in up to a third of DS adults (Cornacchia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Rebillat reported that 77.4% of 31 adults with DS had OSA, and 48.4% had severe OSA. Results were similar to previously reported systematic screening for OSA in 47 non-symptomatic individuals, of whom 72.3% had OSA including 31.9% with severe OSA in Europe [Giménez et al, 2018] and in the USA [Cornacchia et al, 2019]. These data confirm that subjective evaluation underestimates the presence of apneas in individuals with DS and that objective sleep measures and systematic screening are essential.…”
Section: Health Comorbidities In Older Adults With Ds -Assessment and Diagnosissupporting
confidence: 89%
“…Gender does not seem to influence OSA prevalence in adults with DS [ 2 , 14 , 19 , 21 ], whereas in the general population, there is a higher prevalence among males [ 35 ]. There is conflicting evidence on the impact of obesity on OSA prevalence in the DS population, with some studies showing a positive correlation between body mass index and OSA in children [ 45 ] and adults [ 2 , 17 , 20 , 21 , 22 ] but not others [ 14 , 16 , 19 , 37 ]. In the general population, obesity predisposes people to OSA due to excessive fat deposition in the neck and waist, but this relationship is less clear in children and adults with DS [ 21 ].…”
Section: Sleep Disordersmentioning
confidence: 99%